2020
DOI: 10.1128/mbio.01765-20
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analyses of Zika Virus Tropism in Culex quinquefasciatus Reveal Systemic Refractoriness

Abstract: The role of Culex quinquefasciatus in Zika virus transmission has been debated since the epidemic of Zika occurred in the Americas in 2015 to 2016. The majority of studies have found no evidence that C. quinquefasciatus or other Culex species are competent vectors of Zika virus, and the few studies that have proposed Zika vector status for C. quinquefasciatus have relied predominantly on quantitative real-time PCR (qRT-PCR) for viral detection. We assessed the infectious range of pre- and post-epidemic Zika vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 91 publications
(145 reference statements)
1
12
0
Order By: Relevance
“…The rapid spread and severity of the ZIKV epidemic that occurred in the Americas in 2015-2016 has raised suspicions that Cx. quinquefasciatus is an additional vector of this virus (38,39). Some studies suggest that Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid spread and severity of the ZIKV epidemic that occurred in the Americas in 2015-2016 has raised suspicions that Cx. quinquefasciatus is an additional vector of this virus (38,39). Some studies suggest that Cx.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that the previously mentioned experimental studies were conducted under different conditions that may affect or bias the result, such as the origin of the mosquito colonies or animals used for the study, the virus strain and concentration to which they were exposed, and the mode of inoculation (39,68,69). This last aspect is important when it comes to mosquito-borne viruses because it has been observed that vertebrates experimentally exposed via mosquitoes or in combination with mosquito saliva have a higher infection rate compared with needle inoculations (70,71)…”
Section: Discussionmentioning
confidence: 99%
“…Although Aedes mosquitos are the confirmed vector for ZIKV, Culex genera mosquitoes, mostly Culex quinquefasciatus, are theorized to be capable to transmit Zika, further expanding its geographic reach [34]. However, recent studies did not support the ability for Culex mosquitoes to transmit ZIKV [35,36]. In conjunction with its vectors wide global reach, a high proportion of Zika cases are asymptomatic and those who are symptomatic mirror symptoms to dengue and the flu (e.g., fever, rash, muscle and joint pain) compounding the barriers to diagnosis, treatment, and epidemic mitigation efforts.…”
Section: Zika Virusmentioning
confidence: 99%
“…Several flaviviruses that are transmitted by various species of Culex mosquitoes and can cause human illness are associated with birds, including West Nile virus (WNV), Usutu virus, and St. Louis encephalitis virus [ 12 , 13 , 14 ]. To date, no Culex species has been unequivocally confirmed as a competent vector for ZIKV transmission [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The two major vectors of ZIKV for humans, Aedes aegypti and Aedes albopictus , have a wide and expanding geographical range across all continents except Antarctica [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%